Nature’s Involvement in Women’s Self-Completion: An Eco-feminist and Psychoanalytic Criticism on Selected Indonesian Folktales - Santa Maya Pramusita; Antonius Wisnu Yoga Windharto (Institut Agama Islam Negeri Palopo, 2020)
Human beings unavoidably have an innate need to conjugate with other living creatures such as plants and animals. This fundamentally indicates that human builds a sense of connection to nature, that even sometimes they involve nature as one of the symbols in their process of self-completion. They make use of nature in such a way to define themselves as if they possess competencies in accordance with the titles. This paper seeks to find out the depiction of nature in several Indonesian folktales and to disclose how women in those tales are naturally connected with nature and engage it in their self-completion process. Psychological and feminist eco-critical approaches are utilized to answer those problem formulations. Meanwhile, the reason why the researchers only analyze female characters is that they are told in the tales to have an intimate relationship with nature and become the representation of ‘Mother Earth’. The analysis results show that nature in the selected folktales is depicted as pretty chummy to oppressed women. They are so connected that even those women establish nature as their medium to reveal their self-concept as strong, consistent, and honest women